On the "Naturalist" Critique of Clement Greenberg Vide Kant: A Mistaken & Handed-Down Critique - Erkan, Ekin (Cosmos and History: The Journal of Natural and Social Philosophy, 2023)
According to commentators like Rosalind Krauss, Briony Fer, Caroline Jones, and Michael Fried, Clement Greenberg’s formalist/positivist device of “medium-specificity” debars errant affective aesthetic experiences that are embodied; despite significant differences in how these theorists arrive at this conclusion, one shared point of emphasis is Greenberg’s inheriting Kant’s disinterested conception of pleasure in reflective judgments of beauty. Offering a textualist review of Kant’s Analytic of the Beautiful, I seek to demonstrate that neither Greenberg, nor Greenberg’s critics, are correct in their account of Kant’s judgments of beauty. Specifically, I argue that Greenberg conflates Kant’s conception of judgments of free beauty (pulchritudo vaga) with merely adherent beauty (pulchritudo adhaerens). In formulating a rejoinder to Greenberg and the misplacement of Greenberg as a Kantian, and following Diarmuid Costello, I hope to save a path for a Kantian aesthetics of the present, much in the spirit of other broadly Kantian art historians and philosophers of art/aesthetics (e.g., Thierry de Duve, Paul Guyer, Ido Geiger, etc.).